Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Bakmi Kepiting Ahok 36 Kelapa Gading - Christian Halim; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of This study aims to determine the effect of product quality and service quality on consumer satisfaction Bakmi Kepiting Ahok 36 Kelapa Gading. This study uses a quantitative approach. Data was collected by distributing questionnaires using a Likert scale to measure each statement. Samples were taken as many as 105 respondents using purposive sampling technique from Bakmi Kepiting Ahok 36 Kelapa Gading. This research uses validity test, reliability test, classic assumption test, multiple linear regression and hypothesis test with the help of SPSS 23 program. The results show that product quality affects customer satisfaction, service quality affects customer satisfaction and simultaneously product quality and service quality influence on consumer satisfaction at Bakmi Kepiting Ahok 36 Kelapa Gading.